Facilitators for establishing a home-based medicine reverse logistic system in low- and middle-income countries – a scoping review - Vincent, Jose; Anish, Thekkumkara Surendran (Frontiers in Pharmacology, 2025)
BackgroundThe end-of-use and end-of-life medicines at households are often disposed of improperly, which has harmful environmental impacts. Health hazards like antimicrobial resistance can occur. A home/household-based medicine reverse logistics system can avoid improper disposal of medicine waste, and it can recover any remaining value from end-of-use medicines.MethodsWe did a scoping review to identify the key facilitators that help the initiation and establishment of a Medicine Reverse Logistics (MRL) system for the collection of unused medicines from households. Google Scholar and PubMed were the databases searched. A qualitative synthesis of included studies was performed. Themes and subthemes were identified. The keywords used were medicines, drugs, reverse logistics, homes, houses, and households.ResultsThe awareness level of the various stakeholders, the sharing of responsibilities among stakeholders, incentives to stakeholders, political will and legal framework, and the utilization of logistics managerial capabilities of pharmaceutical companies were identified as key facilitators.